More than just buzz: New Zealand bee research and its impact - Dearden, Petra; Dearden, Peter (New Zealand Science Review, 2014)
The honeybee, Apis mellifera, is a remarkable animal. Honeybees are not only unusual and astounding in their biology, but also vitally important to human agricultural productivity. Despite their nasty sting, they are the poster-child for beneficial insects, and one of the few insects that are well loved. They are regarded with warmth and support. They are part of the soundtrack of a long hot summer, the go-to name when we are working hard, and they provide our flavour of choice at breakfast. They have even been incorporated into Kiwiana; every little Kiwi has had a Buzzy Bee. Honeybees play an important role in New Zealand’s economy, production and identity. In this review we aim to present information as to the state and future of New Zealand bees and the beekeeping industry. We would like to review recent advances in bee biology pioneered by New Zealand researchers and show how bee research in New Zealand probes some of the fundamental aspects of bee biology, while also being an exemplar of the way fundamental research often has unforeseen but important applied outcomes.